Programa parental de práticas educativas e seu efeito sobre saúde mental dos pais e perfil cognitivo e comportamental de crianças com TDAH - Ribeiro, Adriana de Fátima (2020)
Parenting practices contribute to the affective and cognitive development of children since the first years of life. These relational aspects become even more important when it comes to families of children with Attention Deficit Hyperactivity Disorder (ADHD). The behaviors often observed in children with ADHD are related to excessive motor activity, planning difficulties, restlessness, inattention, impulsiveness, irritability and school impairment, making them more dependent on their parents' monitoring to organize their behaviors. Caregivers’ guidance programs have proven to be a successful alternative in treating both parent issues and their children's behavior problems. Thus, the project aims to develop, implement and evaluate the effects of a parental intervention program of educational practices on parental emotional difficulties and the effect on cognitive and behavioral aspects of children with ADHD. The sample consisted of 16 participants, four mothers and two fathers, five children with ADHD, between 8 and 11 years old and their respective teachers. The tools for collecting parental data were: a) Parenting Style Inventory (PSI); b) BAI and BDI of the Beck scales (anxiety and depression); c) stress inventory (ISSL); d) quality of life (WHOQOL-bref); e) self-assessment inventory (ASR / 18-59). The instruments to assess children were: a) behavioral inventory for children and adolescents (CBCL-6/18); b) DSM-5-based questionnaire for inattention and hyperactivity signs; c) Attention Deficit Hyperactivity Disorder Scale (Benczik); d) behavioral inventory for children and adolescents (TRF / 6-18); e) Continuous Performance of Conners (CPT); f) Trails test; g) cancellation attention test (TAC); h) Working Memory Index from Intelligence Scale (WISC-IV); i) Five Digit Test (FDT). The study involved seven steps: (1) database analysis (2) group constitution; (3) pre-intervention assessment; (4) application of the parental program; (5) post-intervention assessment; (6) follow up; (7) post-follow up assessment, feedback evaluation and report delivery for the parents. Data from the evaluation instruments were analyzed quantitatively, according to their manuals and compared with their standardization sample. Descriptive analyzes of the information were conducted using simple frequency tables and graphs and comparisons of data regarding children and their parents between the pre, post-intervention and post-follow up phases. In the results of the initial parental evaluation, the presence of some indicators of anxiety, depression and stress was observed. Parenting styles revealed mostly classification within medium, medium low and risk parenting style. Throughout the parenting program it was possible to notice improvements in emotional and behavioral aspects, as well as an increase in positive parenting styles and a decrease in risky educational practices. The main results indicated that the group of children showed improvements in the emotional, behavioral and cognitive skills. Mothers started adopting parenting practices based on positive monitoring and decreased or extinguished the use of negative parenting practices regarding child management. The study concluded that there are evidences that interventions with parents, to develop educational skills for children with ADHD, have benefits for the whole family. Parents develop skills regarding knowledge and management of the disorder and learn to help their children in different aspects, providing school and social development.